ANALISIS LAPORAN KEUANGAN DENGAN MENGGUNAKAN METODE HORIZONTAL PADA BANK RAKYAT INDONESIA AGRONIAGA TBK TAHUN 2016-2019 - Radna Nurmalina (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2020)
This study used a horizontal method to calculate the Return On Assets (ROA) and Return On Equity (ROE) with the data source from Bank Rakyat Indonesia Agroniaga Tbk. Analysis of ROA and ROE of Bank Rakyat Indonesia Agroniaga Tbk during the 2016-2019 period. The conditions of ROA ratio of Bank Rakyat Indonesia Agroniaga Tbk for the last four years have fluctuated from years 2016 to 2019 due to the large operational costs. But the profits are still in rank 3 and 4. The ROE ratio of Bank Rakyat Indonesia Agroniaga Tbk in the last four years has also fluctuated. In 2016 the experienced the decrease -0.12%, 2017 experienced an increase 1.42%, in 2018 the increase was 1.92%, in 2019 it decreased by 1.29%. The state of fluctuation in ROE calculation is caused by global and national economic conditions that affect management in managing Bank Rakyat Indonesia.